118 REGULATION OF FATTY ACID COMPOSITION BY STEAROYL-COA DESATURASE 1 SYSTEMS IN HUMAN HEPATOMA CELLS. Issue 1 (1st January 2007) - Yee, J. K.; Lim, S.; Mao, C. S.; Lee, W. N.P.
Abstract : Background: Stearoyl-CoA desaturase (SCD) is a key enzyme in the synthesis of triglycerides and is a potential target for the treatment of hypertriglyceridemia and obesity. SCD1 is the isoform of SCD highly expressed in the liver and adipose tissue. It catalyzes the conversion of stearate to oleate (C18:0 to C18:1) and palmitate to palmitoleate (C16:0 to C16:1). The effects of SCD1 inhibition in human cell culture are not known. Purpose of the Study: To evaluate the efficacy of two proposed SCD1 inhibitors and their effects on the regulation of fatty acid composition in a human cell culture model using human hepatoma HepG2 cells. Methods: HepG2 cells were grown in culture for 72 hours with [U- 13 C] stearate and [1, 2 13 C]-acetate with (1) DMSO, (2) 10 μM of compound CGX0168 or CGX0290 (generous gifts from CompleGen, Inc.) or (3) 10 μM of trans-10, cis-12 conjugated linoleic acid (CLA). Cell pellets were saponified and fatty acids extracted. Analysis was performed by gas chromatography/mass spectroscopy and the desaturation index was calculated. Summary of Results: In cells cultured with CGX0168, CGX0290, or CLA, the desaturation indices for C18:1 n-9 and C18:1 n-7 were significantly reduced. There was a reduction in the conversion of U-stearate to U-oleate. While CGX0168 and CGX0290 inhibited desaturation of C16:0, CLA did not inhibit C16:0 to C16:1 conversion. CLA also reduced chain elongation of palmitate and palmitoleate, whereas SCD1 inhibitors increased chain elongation activity. Conclusions: The different effects of SCD1 inhibitors and CLA in HepG2 cells demonstrated two separate SCD1 systems: one for the synthesis of C18:1 n-9 and the other for the synthesis of C16:1 n-7, leading to two C18:1 species. The inhibition of these SCD1 systems had different effects on chain elongation of palmitate and palmitoleate. The change in SCD1 activity resulted in changes in fatty acid composition in HepG2 cells through changes in the fatty acid metabolic network.